6ʹʺ‐p‐Coumaroylspinosin protects PC12 neuronal cells from acrylamide‐induced oxidative stress and apoptosis. Issue 9 (27th June 2020) - Li, Yaxin; Zhou, Aimin; Cui, Xusheng; Zhang, Yanqing; Xie, Junbo
Abstract: 6ʹʺ‐p‐coumaroylspinosin (P‐CS) is a flavonoid isolated from Ziziphi Spinosae Semen (ZSS), whereas, the antioxidative activity has not been reported. Oxidative stress is believed to be one of the main causes of neurodegenerative disorders. In this study, the antioxidative effect of P‐CS on PC12 cells was determined. The cells were treated with acrylamide (AA) in the absence or presence of P‐CS, and cell apoptosis was analyzed. Interestingly, P‐CS pretreatment of the cells could significantly prevent AA‐induced cell death, glutathione (GSH) contents decrease, and reactive oxygen species (ROS) overproduction. Further investigation of the molecular mechanism underlying the effect of P‐CS on cell apoptosis revealed that P‐CS was able to suppress the expression of Bax and Bim induced by AA and inhibit the JNKs pathway. Our findings support a role of P‐CS in preventing neuronal cell apoptosis induced by AA, suggesting its therapeutic potential for the treatment of neurodegenerative disorders as a medicinal supplement. Practical applications: Oxidative stress is believed to cause damage in subcellular organelles, nucleic acids, and alteration in protein aggregation as well as disruption of the signaling cascades associated with aging and apoptosis. A small molecule, non‐poisonous natural antioxidant is needed to protect the brain from oxidative stress. Compared with western medicine, natural products carry less risk of adverse effects and are not too expensive, especially for the third‐world countries. Furthermore, ZSS could be used to produce or prepare antioxidants, such as P‐CS, which has been reported significant anti‐oxidative activity in this study. Abstract : PC12 cells were treated with acrylamide (AA) in the absence or presence of P‐CS, and cell apoptosis was analyzed. Interestingly, P‐CS pretreatment of the cells could significantly prevent AA‐induced cell death, glutathione (GSH) contents decrease, and ROS overproduction. Further investigation of the molecular mechanism underlying the effect of P‐CS on cell apoptosis revealed that P‐CS was able to suppress the expression of Bax and Bim induced by AA and inhibit the JNKs pathway.